1999
DOI: 10.1080/001401399184802
|View full text |Cite
|
Sign up to set email alerts
|

Temporal awareness: pivotal in performance?

Abstract: This paper describes an experiment where operators have to deal with various parallel asynchronous processes. The authors were interested in the level of 'temporal awareness' developed by the operator. By temporal awareness, one means the ability of the operator to build a representation of the situation including the recent past and the near future. The hypothesis was that this ability is linked to other elements of performance. The authors also looked at the effects of an aid aimed at supporting the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Indeed, "control can be lost if the available resourcesand especially time -are insufficient to evaluate the current situation and select the next actions" (Hollnagel, 2006, p.246). Grosjean and Terrier (1999) have coined the term "temporal awareness" to emphasize the representation of events in a dynamic situation. Temporal awareness can be defined as the internal representation of events that either have occurred recently or will or could occur in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, "control can be lost if the available resourcesand especially time -are insufficient to evaluate the current situation and select the next actions" (Hollnagel, 2006, p.246). Grosjean and Terrier (1999) have coined the term "temporal awareness" to emphasize the representation of events in a dynamic situation. Temporal awareness can be defined as the internal representation of events that either have occurred recently or will or could occur in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the few empirical studies on this subject, Grosjean and Terrier (1999) found that temporal awareness improved performance both in terms of errors committed and multiple-goal optimisation. However, there is still a lack of conceptual clarity in the concept of temporal awareness and in particular in its relation to overall situation awareness.…”
Section: Temporal Awarenessmentioning
confidence: 99%
“…e.g. De Keyser et al, 1998;Grosjean, 1999;Hoc, 1996). In particular dynamic environments, like the ones which are object of the present study' -that ■106-10 th European Conference on Cognitive Ergonomics evolve also without active interventions of the operator and/or that are characterized by feedback delays -call for feedforward control as the optimal control strategy (Brehmer, 1990).…”
Section: Control Strategiesmentioning
confidence: 99%
“…e.g. De Keyser et al, 1998;Grosjean, 1999;Hoc, 1996). In particular dynamic environments, like the ones which are object of the present study' -that…”
Section: Control Strategiesmentioning
confidence: 99%